Hybridization, diagnostic and prognostic of PEM fuel cells : durability and reliability - Jemeï, Samir (Wiley-ISTE, 2018)
Hydrogen is the most abundant element in the universe. It has a place in the energy mix of the future, especially regarding fuel cells (FCs). This book is an investigation into FCs. Prominence is given to the subject of PEMFCs (proton exchange membrane fuel cells) as they offer interesting perspectives on transport and stationary applications. This being said, a number of technological and scientific obstacles remain to be overcome before an industrial level of development can be reached.